Photo- and electro-luminescent properties of 2, 7-disubstituted spiro[fluorene-9, 9′-xanthene] derivatives containing imidazole-derived moieties. (6th October 2021) - Ma, Hailin; Li, Yuanying; Wu, Shaoguang; Li, Yanmei; Zhao, Yuling; Yang, Hongyan; Su, Wenming; Yu, Tianzhi
Abstract : Two spiro[fluorene-9, 9′-xanthene]/imidazole-derived moiety hybrid compounds were synthesized for OLED applications. Abstract : Two 2, 7-disubstituted spiro[fluorene-9, 9′-xanthene] derivatives, 2, 7-bis(4-(1-phenyl-1 H -benzo[ d ]imidazol-2-yl)phenyl)spiro[fluorene-9, 9′-xanthene] (SFX-2BI ) and 2, 7-bis(4-(1-(4-( tert -butyl)phenyl)-4, 5-diphenyl-1 H -imidazol-2-yl)phenyl)spiro[fluorene-9, 9′-xanthene] (SFX-2IM ), were synthesized by grafting imidazole-derived moieties with different electron-withdrawing abilities onto the 2- and 7-positions of a spiro[fluorene-9, 9′-xanthene] (SFX) core. Their photophysical and electrochemical properties, thermal stability and electroluminescent properties were investigated. The results showed that these compounds have excellent thermal stability and exhibit strong deep-blue emission in dichloromethane solution. In addition, the vacuum-processed doped and non-doped devices based on SFX-2BI and SFX-2IM were fabricated, in which the device prepared using SFX-2BI as the emitting material exhibited the best device performance with a turn-on voltage of 5.5 V, a maximum brightness of 3984 cd m −2, a maximum current efficiency of 3.65 cd A −1 and a maximum external quantum efficiency of 2.61%.